The Evolution of Islamic Educational Institutions from the Classical to the Modern Era: A Historical Analysis of the Transformation of the Islamic Education System - Muhammad Kholid Rafi’i; Abdul Rosyid Teguhdin Hamid (Manunggal Halim Jaya, 2026)
This study aims to analyze the evolution of Islamic educational institutions from the classical to the modern era using a historical approach. Islamic education has undergone transformations driven by social, political, and cultural dynamics, as well as advances in science and technology. During the classical period, Islamic educational institutions developed through kuttabs, mosques, and madrasas, which served as centers for the transmission of Islamic knowledge. As the system moved into the medieval and modern periods, it underwent changes in institutional structures, curricula, teaching methods, and governance in response to the challenges of each era. This study employs a qualitative method using a library research approach. Data were collected from various primary and secondary sources, including books, scholarly articles, national and international journals, and relevant historical documents. The data were analyzed using content analysis and historical analysis to identify patterns in the development of Islamic educational institutions across different periods. The findings indicate that the transformation of Islamic educational institutions has been dynamic while preserving the fundamental values of Islamic teachings. Modernization has encouraged the integration of religious and general sciences, the adoption of technology in the learning process, and the strengthening of professional educational management. Despite the challenges of globalization and digitalization, Islamic educational institutions continue to play a strategic role in developing human resources characterized by integrity and the capacity to adapt to changing times. Therefore, institutional innovation and the improvement of educational quality are crucial to sustaining Islamic education in the modern era.